Phytochemical Screening n-hexane Extract of Sponge Xestospongia testudinaria from Spermonde Archipelago - Septaria Yolan Kalalinggi (Pandawa Institute, 2023)
One of the islands in Indonesia that is inhabited by sponges of various types is the Spermonde Archipelago, which is located in the southern part of the Makassar Strait. Sponge X. testudinaria is one of the sponges that dominates the Spermonde Islands. The difference in environmental conditions where the sponge lives causes the sponge X. testudinaria to have a different adaptation mechanism in producing secondary metabolites as self defense. Research on the of compounds from n-hexane extract sponge X. testudinaria has been carried out using phytochemical tests. Extraction begins with maceration using n-hexane solvent then the solvent is moved using an evaporator. Identification of extract functional groups using IR spectra. The results of the phytochemical screening indicated the presence of alkaloids and steroids which were supported by IR spectrum data indicating the presence of aliphatic NH, C=O and CH groups.